Faktor-Faktor yang Berhubungan dengan Keluhan Low Back Pain Pada Pengendara Ojek Online Gojek di Kawasan Nanggalo - Triana, Nabila; merri, Suks; Seno, Basuki Ario (Jurnal Kesehatan Lingkungan Mandiri, 2022)
One of the groups who are at risk of experiencing Low Back Pain complaints are online motorcycle taxi drivers. This study aims to determine the factors associated with complaints of Low Back Pain in online Gojek motorcycle taxi drivers in the Nanggalo area, Padang City in 2022. The type of research used is quantitative with a cross sectional approach which was carried out from January to March 2022. The population in this study are all Gojek online motorcycle taxi drivers in the Nanggalo area, Padang City with a large sample of 49 Gojek online motorcycle taxi drivers. Data obtained from interviews using questionnaires and observations. Data analysis was carried out univariate and bivariate using Chi square statistical test. The results of the study stated that 61.2% of Gojek online motorcycle taxi drivers experienced complaints of Low Back Pain, 67.3% belonged to a risky age, 57.1% had a risky BMI, 59.2% with a risky work posture, 71.4% with a duration of work. There is a relationship between age (p = 0.028), Posture (p = 0.003) and duration of work (p = 0.001) with complaints of Low Back Pain. Most Gojek online motorcycle taxi drivers in the Nanggalo area in 2022 experience Low Back Pain complaints, to reduce the risk of LBP complaints, it is expected that Gojek online motorcycle taxi drivers to do sports based on age, sufficient food intake, work with a balanced working time and perform an ergonomic work system to minimize the risk of low back pain.